The performance of zero-cost option derivative strategies during turbulent market conditions in developing and developed countries - Lj Basson; Suné Ferreira-Schenk; Zandri Dickason Koekemoer (Cogent Economics & Finance, 2022)
Financial markets behave in a volatile manner at certain stages in their maturity. These volatile conditions pose a market risk to an investor that can be limited by imposing derivatives strategies within the investment objective. The aim of this paper is to provide investors with a trading strategy to effectively manage turbulent market conditions (such as during the Covid-19 pandemic) by implementing a strategy that has a continuous approach of implementation. The study chose to include three main turbulent market periods such as the Dotcom bubble (1995-2005), the financial crisis (2008-2009), and more recently the COVID-19 pandemic (2020). Stock indices from six different stock exchange countries were chosen for comparison (also aligned to different geographical locations and developing versus developed economies) who were most likely to be affected by the extreme market events. Zero-cost collars are option-based strategies that can be used by investors to provide costless protection for stock or index investment. This strategy is obtained by setting equal the price obtained and the price paid for the components of the strategy. Previous literature has to date, not explored the potential outcomes for such procedures of different frequency intervals and the effect thereof on the performance in turbulent and non-turbulent market conditions. It was observed that moderate levels of market volatility combined with high-performing indices provide the scenario for the zero-cost collar to result in respectable returns. Furthermore, in order to add to this performance the strike level of the put option contract needs to be increased. Consequently, respectable results will be produced during periods of both significant market downturns.
Keywords: 330; option contracts; derivative strategies; zero-cost collar; market volatility; COVID-19